Effect of Implementation Ministerial Regulation Number 59 of 2021 on the Sustainability of Stevedoring Companies at Gresik Public Port - Angriani, Rusita; Dahri, M.; Sari, Diyah Purwita; Arisusanty, Dian Junita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research is motivated by existence of a new regulation in the form of Minister of Trasnportation Regulation Number 59 of 2021 which may significantly impact the operations and sustainability of Loading and Unloading Companies (PBM), particularly at Gresik Public Port. The study aims to examine the extent of the regulation’s influence on PBM business continuity. A quantitative approach was used with a survey of 40 PBM respondents at Gresik Port. The research instrument was tested using SPSS, showing valid and reliable results with rcount > rtable (0.412) and Sig < 0.05. The Cronbach’s Alpha value of 0.936 confirms high reliability. Data analysis using simple linear regression reveals a positive relationship between the regulation (independent variable) and business sustainability (dependent variable), with the regression equation Y = 28.867 + 0.777X. The regulation was found to significantly affect PBM sustainability, with a determination coefficient (R²) of 33.3%, indicating that the remaining 66.7% is influenced by other factors. The paired sample t-test also supports the hypothesis that the regulation positively affects business sustainability.